CURRENT PROBLEMS OF DIAGNOSIS AND TREATMENT OF MILD COGNITIVE IMPAIRMENTS IN CHILDREN - G.A. Karkashadze; O.I. Maslova; L.S. Namazova-Baranova (Педиатрическая фармакология)
In practical pediatrics specialists paid wrongly little attention to identification and treatment of cognitive disorders in children. At the same time it is difficult to overestimate the influence of cognitive functions on the formation of human personality and social maladjustment in this part of population. The paper is devoted to the diagnosis and treatment of cognitive impairments. In addition, the classification of this pathology, highlighting aetiopathogenetic factors, prognosis are showed. One of the important problems of early revealing of cognitive impairments and appropriate management of children with this pathology according to the authors opinion are the following: the deficiency of educational programs for training specialists in neurology, lack of knowledge concerning the possibilities of psychological-pedagogical correction, inefficient system of neurological techniques for primary care. Key words: cognitive function, mild cognitive impairment, classification, diagnosis, treatment, prognosis, social maladjustment, psychopedagogical support, children. (Pediatric Pharmacology. — 2011; 8 (5): 37–41.)